THE IMPACT OF FISCAL DECENTRALIZATION ON THE EFFICIENCY OF HEALTH EXPENDITURE AND WELFARE: CASE STUDY OF SOUTH SULAWESI PROVINCE - Azwar, Azwar (Universitas Patria Artha, 2022)
The objective of this study is to analyze: (i) the efficiency level of health function expenditure in the region; (ii) the impact of fiscal decentralization on the efficiency of health function expenditure in the region; and (iii) the implications of health function expenditure efficiency at the level of people welfare in the region. The study used quantitative approaches with Data Envelopment Analysis (DEA) and Dinamic Generalized Method of Moment (DGMM) analysis techniques. The results showed that the realization and utilization of expenditure in most districts/cities in South Sulawesi Province ran less efficient. From the results of DGMM, it was found that Regional Own-source Revenue has a negative and significant impact on the efficiency of health function expenditure, while Balance Funds also have a negative but insignificant effect. Increased efficiency of health function expenditure will be followed by improvements in people's well-being. Meanwhile, fiscal decentralization policies both in the form of Regional Own-source Revenue and Balance Funds, also have a positive effect on welfare, but are limited (insignificant).